Astrocyte to neuron reprogramming with NeuroD1 for repair in canine stroke - Clark, Isaac H.; Roushdy, Zachary; Natera-Rodriguez, Dilmareth; Sun, Kevin; Erlanson, Olivia; Khedr, Shaimaa; Low, Walter C.; Grande, Andrew W. (Frontiers in Stroke, 2025)
Stroke affects hundreds of thousands of people each year and leads to neuronal damage and often long term disabilities. This study served as an exploratory study investigating astrocyte to neuron reprogramming as a potential treatment for ischemic stroke using a canine model to assess anatomical and functional recovery. The study's exploratory nature involved a small sample size, precluding statistically significant conclusions. For treatment, an adeno associated viral (AAV) vector was constructed such that it would target astrocytes and allow expression of NeuroD1 for the intent of reprogramming them into neurons. Animals were analyzed anatomically using MRI scanning, behaviorally with neurological severity score testing, and cellularly with immunohistochemistry staining. Behaviorally, treated animals recovered more rapidly and to a greater extent than controls; anatomically, treated animals also showed much less ventricle enlargement post stroke; and on the cellular level, treated animals showed a decreased level of astrocyte and microglial activation. These findings suggest that NeuroD1-mediated astrocyte reprogramming may reduce neuroinflammation and enhance functional recovery in ischemic stroke, warranting further exploration of this therapeutic approach.